Crisis management in Greece. The shaping of new economic and social balances - Giannitsis, Tassos; Zografakis, Stavros (Düsseldorf, 2017)
"The aim of this study is to explore the impact of the crisis and crisis-induced policies on incomes, inequality and poverty in Greece, to detect the types of adjustment and to show why prevailing perceptions and attitudes caused a heavy economic, social and political cost. Based on extensive income and tax data it investigates the changing relationship between labour, capital and pension income, changes in direct, indirect and property taxation, and their incidence on pre- and post-tax inequality and competitiveness between 2008 and 2012-13. It examines also the losers and the winners and the resulting social reclassifications within the Greek society, the multifaceted types of poverty and inequality and the changing relations between the haves and the haves-not. The analysis distinguishes property and income by main sources at the deciles level, and for the top 1% and 0.1% of the income distribution, at the household and individual level. It covers the period 2008-2015, depending on the available data. It is shown that many economic and social outcomes were the result of deficient approaches and ideological inflexibilities coupled to established political interests, making the exit from the crisis more complicated and painful. A first version of this study was published in March 2015 (Giannitsis and Zografakis 2015). The present edition comprises a deeper and more synthetic analysis and some completely new topics: privileged tax exemptions, structure and taxing of realestate, contribution of female employment on household's income, changes in employment patterns, evolution of the top incomes, effects of low-cost loans before the crisis and their impact on incomes and the banking sector after 2010."